THE PUBLIC DEBATE IN THE TRADITIONAL PRESS ABOUT VIOLENCE AGAINST WOMEN. THE FEMICIDE OF KATHERINE GOMEZ - MEJÍA-NAVARRETE, Julio (2024)
The article sets out the character of the discourse in the traditional press that is disseminated digitally on the case of violence against women, in the emblematic case of Katherine Gómez. The research examines the meaning of words based on their repetition in the media stories and develops the emergence of certain narratives that are oriented from ideological positions of the center, traditional right and extreme right. Big Data techniques are used to collect the messages.